1972
DOI: 10.1104/pp.49.5.690
|View full text |Cite
|
Sign up to set email alerts
|

Solution-Flow in the Phloem

Abstract: Translocation profiles along the path were studied using a modified flap-feeding technique for the simultaneous application of THO and "4C-sucrose. A re-evaluation of a mathematical model for phloem transport with reversible lateral exchange of tracer along the path indicates that lower apparent velocities for THO as compared to labeled carbohydrate are primarily due to extensive lateral exchange of THO along the conduction path. Path-chilling experiments support the concept that THO and "C-sucrose exhibit dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

1972
1972
1992
1992

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…When labeled sugars, dissolved in tritiated H2O, are administered to leaves or petioles, sugars are always transported more rapidly than tritiated H2O in the phloem (1,5,7,9,20). Experiments with bark strips of Salix (16) gave similar results.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…When labeled sugars, dissolved in tritiated H2O, are administered to leaves or petioles, sugars are always transported more rapidly than tritiated H2O in the phloem (1,5,7,9,20). Experiments with bark strips of Salix (16) gave similar results.…”
mentioning
confidence: 99%
“…Some authors, therefore, concluded that mass flow is an unlikely (7,9) or even impossible (15,16) transport mechanism. Others have given preference to the mass flow concept (1,5,20).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This resulted in the recovery of less THO from the path than was theoretically predicted. However, if one assumes that there is an efflux of xylem water into the lamina, which occurs even when the leaf is maintained in a water saturated atmosphere, then it is likely that THO in the phloem of the blade bundles will be continually flushed out (4). A more representative value for C. may lie in the recoverable activity of the secondary or primary veins of the blade which feed into the petiole or path.…”
Section: Analysis Of Modelmentioning
confidence: 99%
“…3, A, scribed here in an effort to demonstrate the similarity of profiles obtained experimentally and theoretically. The 0.6 dm' source leaf of sugar beet was fed using a modified flap feeding method (4) similar to that of Biddulph (2). Velocities were measured for individual plants under study by observing the arrival of "C-translocate at a sink leaf.…”
Section: Analysis Of Modelmentioning
confidence: 99%